Communication Network Structure in Building Environmentally Friendly Behavior (The Case of a Dense Community in Bogor City) - Lasinta, Megafirmawanti; Pandjaitan, Nurmala Katrina; Sarwoprasodjo, Sarwititi (Departement of Communication and Community Development Sciences, Faculty of Human Ecology, 2019)
Efforts to solve environmental pollution in densely populated communities in urban areas are not only the responsibility of the government. Communities as part of social system also have an important role to control the environmental impacts of pollution. One way that community members must do in reducing environmental damage is familiarize environmentally friendly behavior. This research focuses on the analysis of environmentally friendly behavior of Pulo Geulis community members in Bogor City. Pulo Geulis is a Delta in the middle of the Ciliwung River which more or less contributes to whether or not the Ciliwung River is polluted in Bogor City. The communication process is an important factor in changing individual behavior. This study aimed to analyze the structure of community communication networks in developing environmentally friendly behavior. Primary data was obtained through a survey of 100 respondents and in-depth interviews with several informants. Data were analyzed using sociometric methods. The results of sociometric analysis showed that the structure of the community communication network in building community-friendly behavior is a radial personal network. This structure illustrated that community information centers are located in certain individuals such as head of RW, head of RT, or Posyandu cadres. The radial personal network in this study also described the formation of clique, star, bridge, and isolates in the community communication network at Pulo Geulis.